MODERASI BERAGAMA DI ACEH BARAT: NILAI-NILAI MODERASI BERAGAMA DALAM PERSPEKTIF PARA MUFASSIR - Sartina, Ida; Hanif, Hanif (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2022)
This article attempts to address the attitudes of Muslims in West Aceh toward non-Muslims and vice versa, as well as the community's social life within the framework of Islamic moderation principles from the mufassir's point of view. This study employs an ethnographic methodology and qualitative research techniques. This study combines field research that uses West Aceh as a research location with literature studies that serve as a reference source for moderation. The mufassir's measuring sticks for religious moderation are Wasathiyyah (taking the middle ground), Ta'dil (fair), Tawazun (balanced), Tasamuh (tolerance), and Shura (Deliberation). According to the study's findings, religious moderation has been effective in the West Aceh region. People interact with one another in educational, social, buying, and selling situations while assisting one another without distinction of race or religion.